Analisis Kadar Timbal ( PB ) Pada Ikan Cakalang Yang Diperjualbelikan Pada Tempat Pelelangan Ikan Paotere Kota Makassar - Nurasisah Nurasisah; Nurul Utami Halimsyah; Suharsih Thahir (Jurnal Media Laboran, 2018)
Fish as one of the aquatic biota can be used as an indicator of the level of pollution that occurs in the waters. The process of transferring heavy metals from seawater into the body of a fish is very likely to occur, which in turn will adversely affect the fish and humans who consume it. This study aims to determine and determine the levels of lead metal (Pb) on skipjack tuna that are traded at the paotere fish auction site in the city of Makassar with laboratory analysis techniques using organoleptic samples in the form of skipjack meat. Pb heavy metal analysis has been carried out in the samples of skipjack fish using atomic absorption spectrometry (AAS) method. The initial preparation of the footage is done with the fish being washed, meat taken, dried, pounded and filtered to pass 100 mesh, dissolved with the Teflon bomb technique digested until the sample solution is ready for analysis. Analysis parameters with SSA include optimum conditions of analysis, elemental calibration curves, range of concentrations used, feasibility of the test tool and validation of the test method. The results of research on lead levels in 10 samples of skipjack meat were found to contain lead content varied between 0.006 - 0.0486 mg / kg, in accordance with Indonesian National Standard (SNI) 7387: 2009 the maximum limit of lead metal contamination in food was 0.4 mg / kg. Based on the results of the study, skipjack fish at the Makassar city paotere fish auction contain lead with lead levels still below the threshold set by SNI 7387: 2009, so it is recommended to the community to consider the quality of fish before consuming and to the relevant government agencies to do supervision in order to improve the preservation of the underwater world.